Comparison of arrogance in Shahnameh and Bahmannameh based on the ancient story of Bahmannameh - Amiri, Zohreh (2021)
One of the most important aspects of the struggle of warriors and warriors in epic works is the arrogance that is called by the comrades before the start of the hand-to-hand battle. It is accompanied by pride in ancestry, race, and ridicule. Ferdowsi's Shahnameh is full of unique arrogance that has given its poet a special place with special and various skills, so that these styles have been welcomed and imitated by poets after Ferdowsi. In the meantime, Bahmannameh written by Iranshah Ibn Abi Al-Khair has a special place. In this work, the heroes have boasted in different ways before the battle. This study has selected the examples of boasting of the warriors in the two mentioned works and comparing them to examine their advantages and disadvantages in relation to each other.